Ontology-based forecast of the duration of logistics processes in one-of-a-kind production in SME - Deike Gliem; Ulrich Jessen; Sigrid Wenzel; Wibke Kusturica; Christoph Laroque (Logistics Research, 2022)
Due to severe global competition, the project management process for one-of-a-kind production must aim for better risk management and higher efficiency. Despite being critical in order to forecast the duration of logistics processes, intra-enterprise knowledge, historical data from past projects as well as simulation models are not sufficiently utilized in today's practices. To improve the project planning for one-of- a-kind production, a systematic modeling concept and a technical solution approach are developed, which are based on logistics reference processes and an ontology, as a major part of the overall systematic. This paper focuses on the development of the basic structure of the ontology. A use case applies the ontology within a project management toolset to highlight the potentials for process duration forecasting in project management.
Keywords: 650; ontology; forecast; duration of logistics processes; one-of-a-kind production; methodology toolbox; project management